Konsep Pendidikan Karakter Pada Kegiatan Sinau Bareng Komunitas Maiyah Galuh Kinasih Bumiayu - Yuni Suprapto; Eko Handoyo (WASIS : Jurnal Ilmiah Pendidikan, 2021)
The purpose of the study was to determine the concept of character education in Sinau activities with the Maiyah Galuh Kinasih Bumiayu community.The method used is a qualitative research method. For key informants, researchers interviewed maiyah community activists and maiyah congregations of Galuh Kinasih Bumiyau, document studies were used by researchers to find research gaps and research novelties.Data analysis used source triangulation technique with data collection and data reduction. Interviews used in-depth and independent interviews, research questions were used to determine the concept of character education by the Maiyah Galuh Kinasih Bumiayu congregation during Sinau activities together. The results of the study found that there were five main character education in Sinau activities with the Maiyah Galuh Kinasih community including; religious values, the value of tolerance, the value of love for the homeland, discipline and the value of love of science.